Biomechanical report for the IAAF World Championships London 2017 pole vault women's - Gravestock, H.; Bissas, A.; Merlino, S. (Leeds Becket University; Carnegie School of Sports, 2018)
The women`s pole vault final took place on the night of August 6th in good weather conditions. There was great excitement coming into the event given the thrilling Olympic final between Kateríni Stefanídi and Sandi Morris the previous year. Despite this, and entering the competition with the highest personal best, Morris only took the silver medal with 4.75 m. Stefanídi progressed her own world-leading and national records, which secured her the gold medal with a height of 4.91 m. A national record was also achieved for Robeilys Peinado who shared the bronze medal with Yarisley Silva at 4.65 m. (Attention! registration on the IAAF site is required for downloading)